Fragile X syndrome and cerebral perfusion abnormalities: Single-photon emission computed tomographic study - Kabakus, Nimet; Aydin, Mustafa; Akin, Haluk; Balci, Tansel Ansal; Kurt, Abdullah; Kekilli, Ersoy (Sage Publications Inc, 2006)
Fragile X syndrome is an inherited disorder caused by a defective gene on the X chromosome. It is associated with developmental or behavioral symptoms and various degrees of mental retardation. Morphologic abnormalities and altered perfusion of various brain areas can underlie these functional disturbances. The aim of this study was to investigate the cerebral perfusion state in patients with fragile X syndrome using single-photon emission computed tomography (SPECT). Structural and functional assessment was also performed by magnetic resonance imaging (MRI) and electroencephalography (EEG). Eight boys with cytogenetically confirmed fragile X syndrome (mean age 8.8 +/- 4.4 years, range 5-18 years), were included. All patients had mental retardation, with a mean IQ of 58.9 +/- 8.8 (range 40-68), and additional neurobehavioral symptoms. SPECT revealed cerebral perfusion abnormalities in six patients (75%), most commonly in the frontoparietotemporal area and prominent in the right hemisphere. The SPECT and EEG findings were concordant: hypoperfused areas in SPECT corresponded to regions of persistent slow-wave paroxysms on EEG. On the other hand, cranial MRI was abnormal qualitatively only in two patients (25%) showing cerebellar and vermal hypoplasia and cerebral hemispheric asymmetry. Our results indicate that cerebral perfusion abnormalities, which are correlated with electrophysiologic findings but not necessarily with anatomic abnormalities, can underlie the pathogenesis of the clinical findings observed in fragile X syndrome.
Keywords: Epilepsy; Males